New directions in chimeric antigen receptor T cell [CAR‐T] therapy and related flow cytometry. Issue 4 (30th April 2020) - Maryamchik, Elena; Gallagher, Kathleen Mary Ellen; Preffer, Frederic I.; Kadauke, Stephan; Maus, Marcela V.
Abstract: Chimeric antigen receptor (CAR) T cells provide a promising approach to the treatment of hematologic malignancies and solid tumors. Flow cytometry is a powerful analytical modality, which plays an expanding role in all stages of CAR T therapy, from lymphocyte collection, to CAR T cell manufacturing, to in vivo monitoring of the infused cells and evaluation of their function in the tumor environment. Therefore, a thorough understanding of the new directions is important for designing and implementing CAR T‐related flow cytometry assays in the clinical and investigational settings. However, the speed of new discoveries and the multitude of clinical and preclinical trials make it challenging to keep up to date in this complex field. In this review, we summarize the current state of CAR T therapy, highlight the areas of emergent research, discuss applications of flow cytometry in modern cell therapy, and touch upon several considerations particular to CAR detection and assessing the effectiveness of CAR T therapy.